2016
DOI: 10.1080/15592324.2016.1268311
|View full text |Cite
|
Sign up to set email alerts
|

Rice OsERF71-mediated root modification affects shoot drought tolerance

Abstract: Drought is the most serious problem that impedes crop development and productivity worldwide. Although several studies have documented the root architecture adaption for drought tolerance, little is known about the underlying molecular mechanisms. Our latest study demonstrated that overexpression of the OsERF71 in rice roots under drought conditions modifies root structure including larger aerenchyma and radial root growth, and thereby, protects the rice plants from drought stresses. The OsERF71-mediated root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
(38 reference statements)
0
28
0
Order By: Relevance
“…Similarly, an increase in DT in plants was obtained with overexpression of OsERF71, especially in roots (Lee et al, 2017). However, Yu et al (2017) reported that OsERF109 negatively regulated ethylene synthesis and DT in rice.…”
Section: Ethylenementioning
confidence: 86%
“…Similarly, an increase in DT in plants was obtained with overexpression of OsERF71, especially in roots (Lee et al, 2017). However, Yu et al (2017) reported that OsERF109 negatively regulated ethylene synthesis and DT in rice.…”
Section: Ethylenementioning
confidence: 86%
“…ANT (Meng et al, 2015b), ERF53 (Hsieh et al, 2013), ERF-VIIs (Papdi et al, 2015; Yao et al, 2017a), RAP2.6L (Liu et al, 2012), and RAP2.6 (Zhu et al, 2010) in Arabidopsis are induced by ABA to up-regulate DRE- and ABRE- element containing genes. Rice OsERF71 positively regulates ABA signaling to alter root architecture and confer drought tolerance (Lee et al, 2017; Li et al, 2018). The combination of abiotic stresses and ABA also led to the further activation of DREB2s and stress inducible genes (Lee et al, 2016).…”
Section: Integration Of Ap2/erfs With Hormone Responsesmentioning
confidence: 99%
“…To avoid unwanted side effects, the use of spatially or temporally regulated promoters to control ERF expression could also provide success in the field. For example, increased drought tolerance without growth penalty under normal conditions was obtained with rice plants overexpressing OsERF71 specifically in the roots [49] .…”
Section: Ethylene and Crop Yieldmentioning
confidence: 99%